Analisis Karakteristik Wilayah Transmisi Covid-19 dengan Menggunakan Metode K-Means Clustering - Utari, Dina Tri (Jurnal Media Teknik dan Sistem Industri, 2021)
Since the beginning of 2020, Indonesia has become one of the countries affected by the Covid-19 pandemic. Various efforts have been made by the government to prevent wider disease transmission. Large-scale social restrictions are one of the efforts that have been made by the Government. Bali Province is one of the areas where there are quite a lot of community activities, considering that Bali is a tourist destination that is in great demand by local and foreign tourists. This study aims to see the incidence of positive cases of Covid-19 based on the type of Covid-19 transmission that has occurred in all areas of Bali, so that the mitigation design can be adjusted based on the characteristics of the source of infection in various existing areas. The results show that based on the transmission source, it can be grouped into four clusters that have their respective characteristics. The proposed mitigation strategies include restrictions on local transmission and domestic travel for areas in clusters 1, 2, and 3. Meanwhile, restrictions on local transmission and overseas travel are in the 4th cluster.Â Sejak awal tahun 2020, Indonesia menjadi salah satu negara terkena pandemi Covid-19. Berbagai upaya telah dilakukan oleh pemerintah untuk mencegah transmisi penyakit yang lebih luas. Pembatasan sosial berskala besar menjadi salah satu upaya yang telah dilakukan oleh Pemerintah. Provinsi Bali merupakan salah satu wilayah yang cukup banyak terjadi aktivitas masyarakat, mengingat Bali merupakan kawasan destinasi wisata yang banyak diminati wisatawan lokal maupun mancanegara. Penelitian ini bertujuan untuk melihat kejadian kasus positif Covid-19 berdasarkan jenis transmisi Covid-19 yang terjadi di seluruh wilayah Bali, sehingga rancangan mitigasi dapat disesuaikan berdasarkan karakteristik sumber infeksi di berbagai wilayah yang ada. Hasil menunjukkan, bahwa berdasarkan sumber transmisi dapat dikelompokkan menjadi empat cluster yang memiliki karakteristik masing-masing. Usulan strategi mitigasi yang diberikan antara lain pembatasan transmisi lokal dan perjalanan dalam negeri untuk wilayah yang berada pada cluster 1, 2, dan 3. Sedangkan pembatasan transmisi lokal serta perjalanan luar negeri pada cluster ke-4.